Intratympanic Methylprednisolone Injection as First Line Therapy for Idiopathic Sudden Sensorineural Hearing Loss - Mukul Patar; Rupanjita Sangma (Bengal Journal of Otolaryngology and Head Neck Surgery, 2017)
Introduction